Mortality from AIDS and tuberculosis-HIV coinfection in the Chilean AIDS Cohort of 2000-2017 - Carlos Sanhueza-Sanzana; Ligia Kerr; Carl Kendall (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: This article aims to assess the sociodemographic and epidemiological factors associated with AIDS and tuberculosis-HIV coinfection mortality in the Chilean adult population between 2000 and 2017. This is a retrospective observational study, evaluating the incidence density of TB-HIV coinfection mortality in the population over 14 years of age. We used data from the Chilean AIDS Cohort database, 17,512 people enrolled in highly active antiretroviral therapy in the public health system in Chile. The Kaplan-Meier survival function and Cox regression were applied. Incidence density of 0.05 for 39,283 person-years for mortality with TB-HIV coinfection was recorded, with an increase in new cases in people living with AIDS among Aymara and Mapuche indigenous populations. Risk factors included CD4 < 500 cells/mm3 (HR = 3.2; 95%CI: 2.2-4.9), viral load at the start of treatment > 10,000 copies/uL (HR = 1.3; 95%CI: 1.2-1.6). Having high school or higher education (HR = 0.76; 95%CI: 0.6-0.9) is a protective factor for mortality for coinfection. Mortality was concentrated in TB-HIV coinfected people with increasing mortality among women and indigenous populations. The paper contributes to the growing recognition of the role of social determinants in disease outcomes, and the requirement to improve community-focused and community-based testing, sex education in schools, and structural interventions to reduce the adult mortality in Chilean population.